2021
DOI: 10.1051/e3sconf/202128702005
|View full text |Cite
|
Sign up to set email alerts
|

Screening of gallate-based metal-organic frameworks for single-component CO2 and CH4 gas

Abstract: Adsorption using porous adsorbents is widely applied in carbon dioxide (CO2) capture due to its potential energy saving with low operating cost. Metal-organic frameworks (MOFs) are preferable over conventional adsorbents as MOFs have tunable structure properties. Organic linkers from phytochemical-based give a new idea in forming MOFs. Gallic acid is classified under phytochemicals can act as an alternative organic linker in a new family of hybrid framework materials due to low cost, low toxicity, easy availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Carbon dioxide (CO 2 ) and methane (CH 4 ) mixture separation is a key challenge for the energy sector and crucial to provide high purity natural gas that meets gas sales specifications. In our previous reported work, the feasibility of gallate-based MOFs for CO 2 and CH 4 single-component adsorption was predicted using Grand Canonical Monte Carlo (GCMC) simulation [ 9 ]. Among the studied gallate-based MOFs, Mg-gallate showed the highest predicted CO 2 adsorption capacity and CO 2 /CH 4 selectivity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon dioxide (CO 2 ) and methane (CH 4 ) mixture separation is a key challenge for the energy sector and crucial to provide high purity natural gas that meets gas sales specifications. In our previous reported work, the feasibility of gallate-based MOFs for CO 2 and CH 4 single-component adsorption was predicted using Grand Canonical Monte Carlo (GCMC) simulation [ 9 ]. Among the studied gallate-based MOFs, Mg-gallate showed the highest predicted CO 2 adsorption capacity and CO 2 /CH 4 selectivity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reported work, the feasibility of gallate-based MOFs for CO 2 and CH 4 single-component adsorption was predicted using Grand Canonical Monte Carlo (GCMC) simulation [ 9 ]. Among the studied gallate-based MOFs, Mg-gallate showed the highest predicted CO 2 adsorption capacity and CO 2 /CH 4 selectivity [ 9 ]. The magnesium atom exhibits a significant contribution in the conduction band of states, leading to possible Lewis acidic activity in crystalline materials [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to our previous reported work, Grand Canonical Monte Carlo (GCMC) simulation suggested that the nickel gallate metal-organic framework (Ni-gallate) has the potential to serve as a cost-effective adsorbent for the separation of CO 2 and CH 4 based on the predicted unary adsorption isotherms [9]. In addition, Ni-gallate demonstrated remarkable performance in CO 2 and CH 4 adsorption, as indicated by experimental unary adsorption isotherms [10].…”
Section: Introductionmentioning
confidence: 96%
“…A new invention of adsorbents has been found by researchers, which provides a higher adsorption capacity of CO 2 with a higher surface area of solid sorbents compared with conventional adsorbents [7,11]. Currently, multiple promising adsorbents, such as Zeolite 5A, MIL-101 (Cr), Mg-Gallate, and Metal-Organic Frameworks, offer higher CO 2 adsorption capacities [12,13]. The addition of certain binding sites at the pore surface, such as amines acting as Lewis bases and coordinatively unsaturated metal cations actinig as Lewis acids, can improve high absorption under ambient conditions in porous materials [7].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium metal is reported to be the best metal center due to its lighter molecular weight, which is 23.405 g/mol compared with zinc (65.38 g/mol) and nickel (58.69 g/mol) [23]. Ismail et al [13] also worked on MOFs using gallic acid as an alternative linker for enhancing the CO 2 capacity. The authors found that Mg-gallate has a maximum predicted adsorption capacity of 7.79 mmol/g.…”
Section: Introductionmentioning
confidence: 99%